Quantifying capture efficiency of gas collection wells with gas tracers. (September 2015) - Yazdani, Ramin; Imhoff, Paul; Han, Byunghyun; Mei, Changen; Augenstein, Don
Highlights: Developed an in situ gas tracer method for quantification of landfill gas collection efficiency. Gas collection efficiency always exceeding 70% with seven tests showing a collection efficiency exceeding 90%. Poor collection efficiency was associated with a water-laden refuse or remnant daily cover soil. Quantitative data from tracer tests can help assess landfill gas collection and cover system design. Abstract: A new in situ method for directly measuring the gas collection efficiency in the region around a gas extraction well was developed. Thirteen tests were conducted by injecting a small volume of gas tracer sequentially at different locations in the landfill cell, and the gas tracer mass collected from each test was used to assess the collection efficiency at each injection point. For 11 tests the gas collection was excellent, always exceeding 70% with seven tests showing a collection efficiency exceeding 90%. For one test the gas collection efficiency was 8 ± 6%. Here, the poor efficiency was associated with a water-laden refuse or remnant daily cover soil located between the point of tracer injection and the extraction well. The utility of in situ gas tracer tests for quantifying landfill gas capture at particular locations within a landfill cell was demonstrated. While there are certainly limitations to this technology, this method may be a valuable tool to help answer questions related to landfill gas collection efficiency and gas flow within landfills. Quantitative data from tracer tests may help assess the utility and cost-effectiveness of alternative cover systems, well designs and landfill gas collection management practices.